Some Important Issues Of Studying The Methods Of Administrative-Legal Regulation Of Business Activity - Ataev Shakir Kuranbaevich (Academia One Publishing, 2024)
This comprehensive analysis delves into the intricate mechanisms of administrative and legal regulation governing modern business activities. The study explores the multifaceted approaches, tools, and strategies employed by governments and regulatory bodies to oversee, control, and support business operations. Through a systematic examination of case studies and regulations, this research offers valuable insights into the evolving landscape of business regulation, shedding light on its implications for both entrepreneurs and regulatory authorities.
Keywords: business regulation; administrative control; legal framework